Epidemiology of delirium in hospitalized patients in Latin America: A systematic review. (28th July 2022) - Bravo, Maximiliano; Bustos, Sebastian; Acuña, Estefania; Cisternas, Irma; Gutierrez, Pedro; Vega, Daniela P. Ponce de la; Castro, Roberta; Tobar, Eduardo; Maldonado, Jose; Salech, Felipe
Abstract: Background: Accurate epidemiological data are essential for the planning of policies aimed at the identification, prevention, and management of delirium. The reported occurrence of delirium in hospitalized patients varies widely among studies, ranging between 5% to more than 80% in the international literature. The exact occurrence in Latin America is not well described. Objective: The aim of this study is to conduct a systematic analysis of the published data on the epidemiology of delirium in hospitalized patients in Latin America. Methods: We conducted a systematic review following PRISMA guidelines. Both MEDLINE and LILACS databases were searched for original research articles reporting the occurrence of delirium among adult hospitalized patients in Latin American countries. Studies including pediatric populations were excluded from this analysis. Two authors independently applied eligibility criteria, assessed quality, and extracted data. The corresponding authors of the original articles were contacted to obtain relevant information about the study when this was not present in the published manuscripts. Results: Seven hundred and eighteen original articles were identified. After screening titles and abstracts, 149 studies were included in the final analysis. The occurrence of delirium varied depending on the clinical scenario: (1) in the general medico‐surgical wards, it ranged from 2.1% to 60.4%, (2) in the Intensive Care Units (ICUs), from 9.6% to 94.8%, (3) in the post‐operatory population, from 5.45% and 52.3%, and (4) it was found to be between 10.7% and 62% in the emergency department setting. The most used delirium assessment tools were the "Confusion Assessment Method" (CAM; in the general population), and the "Confusion Assessment Method for the ICU" (CAM‐ICU). Fourteen out of 149 studies were conducted in clinical settings who actively implemented some form of non‐pharmacological delirium prevention bundles, most of them as part of ICU sedation‐analgesia protocols. Conclusion: Delirium occurs frequently in hospitalized patients in Latin America throughout a variety of clinical scenarios, including ICU, general wards, post‐operatory populations, and among the emergency department setting. The CAM and the CAM‐ICU are the most used delirium assessment tools. Bundles of non‐pharmacological interventions to prevent delirium are not universally implemented.